Gizi Seimbang pada saat Puasa untuk Meningkatkan Imunitas di Masa Pandemi Covid-19 pada Ibu di Desa Tonasa Kabupaten Gowa - A.Rizki Amelia AP; Reza Aril Ahri (Idea Pengabdian Masyarakat, 2021)
Fasting Ramadan as worship has many benefits for health, so that these two goals can be achieved, it is necessary to regulate diet specifically, especially regulating nutritional intake during iftar and sahur. During fasting the diet will change, because it is only allowed to eat in the morning before dawn and at night. The stomach is left empty for about 13 hours. Generally, the body takes 3-5 days to adapt to a new diet. From the nutritional aspect, fasting will at least reduce nutritional intake, especially energy by around 20-30 percent. This community service activity is carried out using an action study method where mothers in Tonasa Village will practice cooking food according to the nutritional needs needed according to age, then increase knowledge and understanding of balanced nutrition during fasting for PKK mothers in RW 01 In addition, we as a service team will provide tips so that families can continue to do activities without feeling weak. The education provided is about balanced nutrition when fasting through Pre and Post Tests. The implementation time of the service is carried out for 4 months. The expected result of this service is that it can increase the knowledge and skills of mothers regarding a balanced nutritional menu during fasting.